Determinants of Public Intention and Acceptance Behavior Toward Biomass Supply for Electricity Generation: The SEM-PLS Approach - Meiri Triani; Ahyahudin Sodri; Haruki Agustina (Jurnal Ilmu Ekonomi Terapan, 2026)
Objective: This study aims to examine the determinants of public acceptance behavior regarding biomass provision for co-firing in coal-fired power plants (CFPPs), to encourage community participation in supporting the sustainability of biomass co-firing initiatives while promoting circular economy practices in the transition toward low-carbon energy systems. Methods: A quantitative survey was conducted using a conceptual model based on the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), extended by integrating the information dissemination variable to examine public intentions and behaviors regarding biomass energy. Data from 414 individuals were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Findings: The results show that attitude and perceived behavioral control are the strongest predictors of intention, while intention has a substantial effect on community participation behavior (path coefficient = 0.594). The model explains 35.3% of the variance in behavior, indicating a moderate level of explanatory capability. Information dissemination significantly strengthens both attitudes and perceived behavioral control. Originality: This study addresses a gap in the existing literature by examining public intention and acceptance regarding biomass provision within a developing country context in Indonesia. Practical/Policy implication: The findings of this study highlight the importance of collaboration among stakeholders in designing community engagement programs that effectively communicate the practical benefits of participation to local communities.